Leadership, management and teamwork learning through an extra-curricular project for medical students: descriptive study - Jorge, Maria Lucia da Silva Germano; Coelho, Izabel Cristina Meister; Paraizo, Mariana Martins; Paciornik, Ester Fogel (São Paulo Medical Journal, 2014)
CONTEXT AND OBJECTIVE: Professionalism in medicine requires preparation for the globalized world. Our objective was to describe a project that introduces medical students to the community, hospital and laboratory activities, thereby allowing them to gain experience in people management, leadership and teamwork. DESIGN AND SETTING: Descriptive study of the process applied at a philanthropic medical school in Curitiba, Paraná. METHOD: Inclusion of management and leadership practices as part of the medical degree program. RESULTS: The study groups consisted of fifteen students. After six months, any of the participants could be elected as a subcoordinator, with responsibility for managing tasks and representing the team in hospital departments and the community. The activities required increasing levels of responsibility. In medical schools, students’ involvement in practical activities is often limited to observation. They are not required to take responsibilities or to interact with other students and stakeholders. However, they will become accountable, which thus has an adverse effect on all involved. The learning space described here aims to fill this gap by bringing students closer to the daily lives and experiences of healthcare professionals. CONCLUSION: Being a physician requires not only management and leadership, but also transferrable competencies, communication and critical thinking. These attributes can be acquired through experience of teamwork, under qualified supervision from teaching staff. Students are thus expected to develop skills to deal with and resolve conflicts, learn to share leadership, prepare others to help and replace them, adopt an approach based on mutual responsibility and discuss their performance.